Changes in stroke kinematics during resisted and assisted freestyle swimming - Williams, B. K.; Sinclair, P. J.; Galloway, M. (ISBS - Conference Proceedings Archive (Konstanz), 2006)
Ten subjects swam 50m freestyle trials using; resisted (RS), assisted (AS), and free swimming (FS). Data from 2 underwater cameras were combined to provide a 3-D reconstruction of each trial. During RS, the stroke length (SL), mean 3D resultant hand velocity and average forward velocity (AV) significantly (p < 0.05) decreased compared to the FS trial. During RS, the swimmers were unable to generate enough force to prevent the tether from slowing them down. Further, calculations suggest that the average propulsive force acting on the swimmer was not increased during RS. During the AS trial SL, stroke rate and AV increased, while maximum hand depth decreased relative to the FS trial. There appear to be some positive benefits, however the technique changes found during both RS and AS result in these forms of training remaining questionable.